Our promised land : faith and militant Zionism in Israeli settlements - Selengut, Charles (Rowman and Littlefield, 2015)
"Our Promised Land takes readers inside radical Israeli settlements to explore how these settlements were formed, what the people in them believe, and their role in Israel and the Middle East today. Drawing on three years of research in these settlements, Our Promised Land offers an in-depth exploration of a topic that is often mentioned in headlines but little understood. Attempting to take a neutral perspective on a contentious topic, the book offers an overview of settlements in Israeli past and present, filled with the voices and stories of people who live there"--Provided by publisher.